Solar-powered wireless sensors network - transmission part - Fan, Sijia (Nanyang Technological University, 2022)
Solar-powered wireless sensor network: A wireless power transmission system is designed to integrate a photovoltaic charging module into the inside facade of a facility or building and use it to power a few LoRa sensor nodes distributed in that region. It can be used to directly power an array of sensors or an RF transmitter to indirectly power a network of sensors within the room. The need to replace batteries in sensor nodes is entirely eliminated. The energy that is usually lost to the environment is reused, therefore enabling the wireless sensor network to be carbon neutral. It is aimed at being used in a live environment that has ambient light, such as an office. Once the light is on, the small solar panels will convert the ambient light energy into DC power through some energy harvesting components and store the energy in the battery. Then the battery will power up the transmitting devices, in turn powering up the LoRa sensors. The hardware core of the transmitting part uses a power bank charging module, a transmitter device, an RF antenna, and an evaluation board. The power bank charging module is used to transmit the power in the battery to the transmitter in the form of a USB port. The transmitter is used to convert the DC power to RF energy and wirelessly transmit the power to the evaluation board. The evaluation board is used to convert the RF energy back to DC power. The technologies involved are as follows: Wi-Fi network communications, RF harvesting technologies, low-powered LoRa protocol communications, and database programming. With the help of an abundance of open-source libraries, the development time to completion is much reduced.